Analisis Penyelenggaraan Sistem Aplikasi E-Samsat Kepri dalam Pembayaran Pajak Kendaraan Bermotor oleh Badan Pengelolaan Pajak dan Retribusi Daerah Provinsi Kepulauan Riau - Edward Mandala; Bely Putra Handaresta; Rendra Setyadiharja; Agus Sujono (STISIPOL Raja Haji, 2022)
The Riau Islands E-Samsat is an application issued by the Regional Tax and Levy Management Agency of the Riau Islands Province to taxpayers through an integrated application. In a policy taken by the government as it seeks to improve the national economy through paying motor vehicle taxes, which so far have not been optimal in the process of using the application system in a fast time and must be passed to pay motor vehicle taxes. The Riau Islands E-Samsat will also be developed and upgraded in the future for motor vehicle tax services. The formulation of the problem in this study is how the implementation of the Riau Islands E-Samsat Application System in Payment of Motor Vehicle Taxes by the Regional Tax and Rtribution Management Agency of the Riau Islands Province which aims to determine the effectiveness of the Riau Islands E-Samsat application system program for motor vehicle tax payments. In this study, the researcher will use a qualitative approach research method with a descriptive analytical method with a number of informants as many as 7 people, therefore this study will interview 1 staff from BP2RD Riau Islands Province, 1 staff from Samsat UPT PPD Tanjungpinang City and 5 mandatory people. motor vehicle tax in Tanjungpinang City. The results of this study indicate that the implementation of the Riau Islands E-Samsat Application System to pay motor vehicle taxes issued by the Riau Islands Province BP2RD has been running well but there are still shortcomings and sometimes it is not effective. To provide suggestions for opinions or suggestions that are still lacking, in application-based motor vehicle tax payment services such as internet constraints and lack of socialization to the public who still do not understand and understand how to use the application so that the Regional Tax and Levy Management Agency of the Riau Islands Province must provide clear directions to taxpayers so that future taxpayers will understand how to use the Riau Islands E-Samsat application for motor vehicle tax payments.